2014
DOI: 10.2337/db13-1784
|View full text |Cite
|
Sign up to set email alerts
|

Recessive Mutations in PCBD1 Cause a New Type of Early-Onset Diabetes

Abstract: Mutations in several genes cause nonautoimmune diabetes, but numerous patients still have unclear genetic defects, hampering our understanding of the development of the disease and preventing pathogenesis-oriented treatment. We used whole-genome sequencing with linkage analysis to study a consanguineous family with early-onset antibody-negative diabetes and identified a novel deletion in PCBD1 (pterin-4 α-carbinolamine dehydratase/dimerization cofactor of hepatocyte nuclear factor 1 α), a gene that was recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 24 publications
1
39
1
Order By: Relevance
“…Re-evaluation of earlier identified patients with this syndrome revealed that hypomagnesemia and MODY5-like diabetes are later manifestations of PCBD1 mutations [53, 54]. This finding also has implications for the importance of looking for alternative genetic diagnoses (including PCBD1 mutations) if screening for mutations of PAH (phenylalanine hydroxylase) is negative after a positive result for the Guthrie test.…”
Section: Hereditary Hypomagnesemiasmentioning
confidence: 99%
“…Re-evaluation of earlier identified patients with this syndrome revealed that hypomagnesemia and MODY5-like diabetes are later manifestations of PCBD1 mutations [53, 54]. This finding also has implications for the importance of looking for alternative genetic diagnoses (including PCBD1 mutations) if screening for mutations of PAH (phenylalanine hydroxylase) is negative after a positive result for the Guthrie test.…”
Section: Hereditary Hypomagnesemiasmentioning
confidence: 99%
“…Simaite et al observe an abundant expression of Pcbd1 in the developing pancreas of both mouse and Xenopus embryos [51]. The genetic evidence obtained by them displays that PCBD1 variations can lead to early-onset nonautoimmune diabetes with characteristics like dominantly inherited HNF1A-diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In the pancreas, heterozygous mutations in DCoH1 that cause mild neonatal hyperphenylalaninemia also increase the risk of monogenic diabetes (50). Mutations in HNF-1␣ cause maturity-onset diabetes of the young type 3 (MODY3) (51).…”
Section: Discussionmentioning
confidence: 99%